Tri Hita Karana as the Foundation of Character Education in SMP 4 Singaraja: An Ethnopedagogical Perspective - Ida Bagus Rai Putra; Beatus Tambaip; I Gede Bagus Wisnu Bayu Temaja; I Wayan Rupa; Ni Luh Komang Candrawati; Ni Wayan Aryani; I Gusti Ayu Armini (International Journal of Education, Vocational and Social Science, 2023)
Ethnopedagogy is the actualization of learning that is oriented to local wisdom values. The concrete embodiment of local wisdom values can be found in character education. The concept of ethnopedagogy is used in formal school learning, including SMPN 4 Singaraja. This study aimed to identify the role of ethnopedagogy based on Tri Hita Karana as character education at SMPN 4 Singaraja. This research was a descriptive qualitative type. The object of this study was the role of ethnopedagogy based on Tri Hita Karana as character education, while the subjects of this study were students of SMPN 4 Singaraja. The data were collected through observation, discussion, in-depth interviews, and involved participation. The data were analyzed with descriptive methods. Based on the analysis, student character can be formed from an exciting learning process and habits taught at school. Developing student character takes work, and many ways exist to create student character in a much better direction. Collaboration between teachers, students, parents, and the community is one of the keys to successfully forming student character. Tri Hita Karana’s ethnopedagogy in schools is the foundation for developing students’ character following the values of character education, namely the Parahyangan, which focuses on teaching religious values. Pawongan, moral character values, tolerance, democracy, respect for achievement, friendship, and social care. Palemahan, the importance of character education that teaches care for the environment.